Perceptual inference and autistic traits. (April 2015) - Skewes, Joshua C; Jegindø, Else-Marie; Gebauer, Line
Autistic people are better at perceiving details. Major theories explain this in terms of bottom-up sensory mechanisms or in terms of top-down cognitive biases. Recently, it has become possible to link these theories within a common framework. This framework assumes that perception is implicit neural inference, combining sensory evidence with prior perceptual knowledge. Within this framework, perceptual differences may occur because of enhanced precision in how sensory evidence is represented or because sensory evidence is weighted much higher than prior perceptual knowledge. In this preliminary study, we compared these models using groups with high and low autistic trait scores (Autism-Spectrum Quotient). We found evidence supporting the cognitive bias model and no evidence for the enhanced sensory precision model.